Jacques Derrida and the humanities : a critical reader - Cohen, Tom, 1953- (Cambridge University Press, 2001)
This volume is a trans-disciplinary collection dedicated to Jacques Derrida's work. The assembled contributions constitute an investigation of the role of his work within the field of humanities, present and future.